THE MEDIATING EFFECT WORK ENGAGEMENT ON THE RELATIONSHIP BETWEEN PAY SATISFACTION AND TEACHER CREATIVITY AT SMK “XYZ” IN SIDOARJO - Parameswari , Yedida Nindya; Wulani, Fenika (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
The study aims to identify the relationship between pay satisfaction and creativity among SMK “XYZ” teachers in Sidoarjo and the mediating role of work engagement in the relationship. Data was collected by distributing the questionnaire. There were 117 teachers who were respondents in our study. The results of testing using PLS-SEM showed that the influence of pay satisfaction on creativity is not significant, but pay satisfaction significantly increases work engagement. The study finds that work engagement has a positive influence on teacher creativity. Furthermore, the results indicated that work engagement mediates the effect of pay satisfaction on the creativity of teachers. Thus, teachers who are satisfied with their pay have higher work engagement, which further increases their creativity